Design Of A Monitoring System For Potential Of Hydrogen (Ph) In Fish Aquarium Water Based On ESP-32 Microcontroller - Rizkia, Aditya Awal; Husain, Adam (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2024)
Measuring the quality and health of water in a decorative fish tank can be simplified by regularly monitoring the water pH. However, this pH monitoring is often neglected by aquarium owners due to work commitments, household responsibilities, or when they have to leave home for an extended period of time. This research designed a water pH monitoring system in an ornamental fish aquarium using a pH sensor and an ESP-32 microcontroller that can remind users through a telegram Bot message and can be seen through the LCD using the waterfall development method as a method of making tools in this study. Based on the research that has been done, the automatic pH reading system has been successfully built by being accessed via telegram and can be seen on the LCD display. pH Sensor testing has an accuracy value of 90% with testing using litmus paper comparison.